Misremembrance of Things Past: Depression Is Associated With Difficulties in the Recollection of Both Specific and Categoric Autobiographical Memories. (July 2019) - Hitchcock, Caitlin; Rodrigues, Evangeline; Rees, Catrin; Gormley, Siobhan; Dritschel, Barbara; Dalgleish, Tim
Impaired retrieval of specific, autobiographical memories of personally experienced events is characteristic of major depressive disorder (MDD). However, findings in subclinical samples suggest that the reduced specificity phenomenon may reflect a broader impairment in the deliberate retrieval of all autobiographical memory types. This experiment ( N = 68) explored this possibility by requiring individuals with and without MDD to complete a cued-recall task that required retrieval of specific, single-incident memories to a block of cues; retrieval of categoric, general memories to a block of cues; and to alternate between retrieval of specific and general memories for a block of cues. Results demonstrated that relative to never-depressed controls, individuals with MDD experience reduced recall of both specific ( d = 0.48) and general memories ( d = 1.00) along with reduced flexibility in alternating between specific and general memories ( d = 0.90). Findings support further development of autobiographical memory–based interventions that target a range of retrieval deficits rather than specificity alone.